PENANGGULANGAN PELACURAN DITINJAU DARI PERSPEKTIF HUKUM DAN GENDER - awitri Nandari, Ni Putu (Jurnal Studi Jender SRIKANDI, 2012)
In this decade, the development of prostitute becomes luster especially in Denpasar city. The government of Denpasar was did some efforts to solve that problem by producing regional regulation no. 2 about ?The Elimination of Prostitute?. In the implementation, the prostitute prevention was much done by ordering and catching the women as the whore done by the upholds law agencies, meanwhile the men as the consumer were free. This way shows that there is an injustice of gender un the effort of prostitute prevention in Denpasar. The injustice of gender causes the difficulties to prevent the prostitute because it is a paradigma of interaction between woman and out of marriage. In That interaction, the woman is like a hire part, meanwhile the man as the consumer or tenant part. In the prostitute prevention that was already done, only the woman as the hire part got punishment; on the other hand the tenant part was free.It shows that the law was made by man and has a purpose to strengthen the patriarchy relationships. Therefore, the theory of law system by Lawrence M. Friedman and the theory of law with feminism perpective by D. Kelly Weisberg are used to analyse that problem
Keywords: PELACURAN